Brodskij a Firenze: An Unpublished Poem by Mario Luzi (ENTHYMEMA, 2024)
The article aims to present an unpublished poem by Luzi, discovered in one of his personal diaries, currently held at the Gabinetto Vieusseux. The poem, titled Brodskij a Firenze, dates to 1995 and serves as Luzi’s response to the criticism made by Brodskij during his visit to Florence in the spring of that year. The first paragraph delineates the background of the conflict between the two protagonists, which can be traced back to Luzi’s endeavor to promote his work in Sweden through the publisher Oreglia, with the hope of achieving the Nobel Prize. The second paragraph chronicles the various phases of the dispute: Brodskij’s arrival in the city, his accusation at the Italian colleague of harboring excessive aspirations for the Swedish prize, Luzi’s responses in newspapers, and the ensuing public and private reactions. In the third paragraph, finally, the unpublished poem is presented, explicated philologically, and subjected to critical analysis.
Keywords: Mario Luzi; Iosif Brodskij; Dispute; Nobel Prize; Unpuplished Poem; Florence